“Space-Strike Weapons” and the Soviet Response to SDI. - Westwick, Peter J. (Diplomatic History, 2008)
The article discusses the U.S. Strategic Defense Initiative (SDI) during the term of U.S. President Ronald Reagan. The author reflects upon the history of the science and technology involved in the program as well as considering the political and diplomatic aspects arising from SDI. General Secretary Mikhail Gorbachev responded to the American initiative by tying nuclear nonproliferation talks to the cessation of SDI. The article also discusses the expansion of defense technologies research such as nuclear powered microwave technologies, X-rays, plasma physics, and electromagnetic fields which were explored by both the U.S. and the Soviet Union during the Cold War, including the various limitations upon such technologies.